Gut Microbiome as a Potential Factor for Modulating Resistance to Cancer Immunotherapy - Shui, Lin; Yang, Xi; Li, Jian; Yi, Cheng; Sun, Qin; Zhu, Hong (Frontiers in Immunology, 2020)
Gut microbiota refers to the diverse community of more than 100 trillion microorganisms residing in our intestines. It is now known that any shift in the composition of gut microbiota from that present during the healthy state in an individual is associated with predisposition to multiple pathological conditions, such as diabetes, autoimmunity, and even cancer. Currently, therapies targeting PD-1/PD-L1 or CTLA-4 are the focus of cancer immunotherapy and are widely applied in clinical treatment of various tumors. Due to relatively low overall response rate, however, it has been an ongoing research endeavor to identify the mechanisms or factors for improving the therapeutic efficacy of these immunotherapies. Other than causing mutations that affect gene expression, some gut bacteria may also activate or repress the host’s response to immune checkpoint inhibitors. In this review, we have described recent advancements made in understanding the regulatory relationship between gut microbiome and cancer immunotherapy. We have also summarized the potential molecular mechanisms behind this interaction, which can serve as a basis for utilizing different kinds of gut bacteria as promising tools for reversing immunotherapy resistance in cancer.